TANGGUNG JAWAB PEJABAT PEMBUAT AKTA TANAH (PPAT) DALAM PEMBUATAN AKTA JUAL BELI YANG DIBUAT TANPA SEPENGETAHUAN DAN PERSETUJUAN PEMILIK OBJEK DALAM PUTUSAN NOMOR 347/PDT.G/2017/ PN.JKT.TIM - Kevin Hernando Pratama; Gunawan Djajaputra (Jurnal Hukum Adigama, 2021)
In making a land deed, PPAT is required to have skills, accuracy, and ability in the field of land law and must be based on the knowledge or approval of the owner of the land object. The problem faced is how is the responsibility of the Land Deed Making Officer (PPAT) in making the sale and purchase deed made without the knowledge and approval of the object owner related to Decision Number 347/Pdt.G/2017/PN.Jkt.Tim. The research method used is normative juridical law research. The results showed that the PPAT that made AJB without the knowledge and approval of the object owner related to the East Jakarta District Court Decision Number 347/Pdt.G/2017/PN.Jkt.Tim is an act against the law and violates the provisions of Article 1365 of the Civil Code, because it is against the law. The principles of propriety, thoroughness and prudence as well as contrary to the legal obligations of the perpetrator so that it causes harm to the Plaintiff. Criminally, PPAT can be charged with Article 263 paragraph (2) of the Criminal Code. Administratively, PPAT can be dishonorably dismissed. In order to avoid misuse of identity and forgery of signatures in the making of PPAT deeds, PPATs are required to attach letters and documents as well as the fingerprints of those who appear on the Minutes of Deed as one of the obligations that must be carried out by Notaries.